A 200-nW 7.6-ENOB 10-KS/s SAR ADC in 90-nm CMOS for Portable Biomedical Applications. (October 2016) - Nazzal, Tasnim B.; Mahmoud, Soliman A.; Shaker, Mohamed O.
Abstract: This paper presents an 8-bit low-power clock gated successive approximation analog to digital converter (SA-ADC) using D-flip flop (D-FF) unit for biomedical applications. The architecture of the proposed SA-ADC is implemented using the sample and hold (S/H) circuit which is based on a sampling transistor with dummy switch, double-tail dynamic latched comparator, the traditional binary weighted capacitor array single ended DAC and a modified clock gated successive approximation register (SAR) controller logic. The SAR controller is implemented using D-FF. The layout and extraction of the proposed low-power clock gated SA-ADC using D-FF unit are done using L-edit and simulated using 90 nm CMOS technology file on LT-spice-IV. According to the simulation results, the low-power clock gated SA-ADC using D-FF unit consumes 200 nW from 1 V power supply without additional calibration or analog circuits. It has signal-to-noise ratio (SNR) of 53.8 dB, peak spurious-free dynamic range (SFDR) of 54.2 dB, and a signal-to-noise-and distortion ratio (SNDR) of 48 dB for a 250 Hz full scale input sine wave. It has also an effective number of bits (ENOB) of 7.6-bits, and a figure of merit (FOM2 ) of 0.1 pJ/Conversion-step. It achieves +0.34/−0.3 and +0.79/−0.58 of Differential non-linearity (DNL) and integral non-linearity (INL) errors respectively. Furthermore, the low-power clock gated SA-ADC using D-FF unit consumes 88.76 nW from 0.85 V power supply without additional calibration or analog circuits. With 0.85 V supply voltage, it has SNR, SFDR and SNDR of 54.6 dB, 39.19 dB and 37.92 dB respectively for the same input sinewave. It achieves ENOB of 6-bits with (FOM2 ) of 0.13 pJ/Conversion-step. It has DNL and INL of +0.38/−0.28 LSB and +0.9/−0.85 LSB respectively. The digitized of real recorded beta EEG signal is precisely reconstructed by the proposed SA-ADC.